Sintesis dan Karakterisasi Zeolit X dari Fly Ash Batu Bara Menggunakan Metode Sintesis pada Suhu Rendah: Synthesis and Characterization of Zeolite X From Fly Ash Waste Using Synthesis Method at Low Temperature - Rieswana, Yuried; Aisyah, Aurela Naura; Sani; Suprihatin (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2024)
Many industries in Indonesia have switched to using coal fuel. The use of coal at PT PLTU Paiton has reached 250 tons per hour and produces 4% of waste by-products of combustion contained from bottom ash by 25% and fly ash by 75%. Fly ash waste will harm the environment and health. Fly ash contains many components, including SiO2 52%, Al2O3 31.86%, Fe2O2 4.89%, CaO 2.68%, and MgO 4.66%. This research aims to synthesize and characterize zeolite X from PT Paiton fly ash using a low-temperature synthesis method. Zeolite X synthesis in this study has 3 steps: The pretreatment process, silica synthesis process, and zeolite synthesis process. The results of silica synthesis obtained SiO2 55.54%. The resulting zeolite product has a typical peak at 2Ï´ 28.72. Zeolite x has a wavelength of 430, 570, 695,7, and 965,7, which respectively indicates Si-O-Si and Si-O-Al bonds, double ring bonds, T-O ring symmetric strain (internal), and asymmetric (internal). The results of zeolite X crystal synthesis in this study could not be formed in the variable of adding time of 3-5 hours with a variation of moles of Al2O3 0,5-1,5 moles.